Development and Validation of an Instrument to Measure Teachers’ Professional Agency during Curriculum Reform and Its Underlying Structure - Mohamed, Lawsha; Binti Tunku Ahmad, Tunku Badariah (IIUM Journal of Educational Studies, 2019)
The purpose of this study was to construct validate an effective instrument to measure teachers’ professional agency and factors influencing it. The validity and reliability of the instrument were tested using exploratory factor analysis and reliability analysis. Ninety-four items were developed for initial instrument based on ecological model of teachers’ professional agency as the conceptual model. An exploratory factor analysis revealed that nine factor structure of the instrument explained 76.37% of the variance in the pattern of relationships among the items. All the nine factors had high reliabilities (all Cronbach’s alpha greater than .791). Fifty-three items remained in the final questionnaire after deleting items with cross-loadings on multiple factors and loadings below .5. Hence this study confirmed a nine-factor structure of the instrument. This instrument could be used to gain a better understanding of the factors influencing teachers’ professional agency during a curriculum reform.